Temporality as Value: Ethnography and the Question of Time. (January 2016) - Kumar, Ratheesh
How does the question of temporality get translated into the register of values in the process of constructing knowledge through ethnography? Is there a possibility of critical ethnography that tracks politics of time in the accounts of the other? By centring these questions to the domain of ethnographic endeavours in Indian anthropology, this article takes a look into the shifting locations of self and the other in the practice of ethnography with reference to the notion of temporality as value. Ethnography, once a key device of anthropological research, has become one of the significant approaches in almost all social science disciplines today and even in certain domains of humanities, management and market research. Ethnography itself has been reimagined and reshaped under different terrains of interdisciplinary approaches. But one would rarely find accounts of political and ideological manoeuvring of temporal concepts and value orientations which inform the theories and rhetoric in it. It pronounces upon the knowledge gathered from such research a discourse which construes the other in terms of a distance from the self, both spatial and temporal. Drawing upon this register of 'time' from the writing of Johannes Fabian, the article transposes the framework to understand the currents in contemporary Indian anthropology.